2021
DOI: 10.1227/neu.0000000000001754
|View full text |Cite|
|
Sign up to set email alerts
|

Does Neuromodulation Reduce Chronic Pain Patient Emergency Department Utilization?

Abstract: BACKGROUND:Chronic pain (CP) affects roughly 100 million adults in the United States. These subjects present disproportionately to the emergency department (ED). Neuromodulation (NM) has been shown to reduce ED visits longitudinally in subjects.OBJECTIVE:To compare ED utilization rates between subjects with CP with and without NM.METHODS:Subjects with failed back surgery syndrome, complex regional pain syndrome, or neuropathic pain diagnosis who visited the hospital between January 1, 2019, and December 31, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Interestingly, Figueroa et al found certain factors that may predict a higher probability for CLBP subjects to seek ED services. These factors include younger age, lower income, near hospital housing, and opioid use at baseline; however, only opioid use was a significant predictor of seeking ED service in subjects with CLBP who underwent neuromodulation therapy [49].…”
Section: Emergency Department Servicementioning
confidence: 87%
“…Interestingly, Figueroa et al found certain factors that may predict a higher probability for CLBP subjects to seek ED services. These factors include younger age, lower income, near hospital housing, and opioid use at baseline; however, only opioid use was a significant predictor of seeking ED service in subjects with CLBP who underwent neuromodulation therapy [49].…”
Section: Emergency Department Servicementioning
confidence: 87%
“…In the article appearing in volume 90, pages 131-139 of Neurosurgery , entitled “Does Neuromodulation Reduce Chronic Pain Patient Emergency Department Utilization?,” there was an error. 1…”
mentioning
confidence: 99%